KUALITAS AUDIT MEMODERASI HUBUNGAN CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE - Rani Putri Anggraeni (2021)
This study aims to analyze the effect of institutional ownership and corporate social responsibility on tax avoidance with audit quality as a moderating variable in mining and coal companies listed on the Indonesia Stock Exchange in 2017-2019. This study is a quantitative research that uses secondary data. The method of data collection is by literature study sourced from the company's annual report. The sample in this study amounted to 39 mining and coal companies selected using purposive sampling method. The data analysis technique used the regression model selection test, classical assumption test, multiple regression, and hypothesis testing. Based on the results of data testing, it can be concluded that (1) Institutional ownership has no significant effect on tax avoidance, (2) Corporate social responsibility has a significant positive effect on tax avoidance, (3) Audit quality weakens the effect of institutional ownership on tax avoidance, and (4) Audit quality strengthens the effect corporate social responsibility and tax avoidance.